The Global Distribution of College Graduate Quality - Martellini, Paolo; Schoellman, Todd; Sockin, Jason (Journal of Political Economy, 2024)
We measure college graduate quality—the average human capital of a college’s graduates—for graduates from 2,800 colleges in 48 countries. Graduates of colleges in the richest countries have 50% more human capital than graduates of colleges in the poorest countries. Migration reinforces these differences: emigrants from poorer countries are highly positively selected on human capital. Finally, we show that these stocks and flows matter for growth and development by showing that college graduate quality predicts the share of a college’s students who become inventors, engage in entrepreneurship, and become top executives both within and across countries.